Alteration of pulmonary mitochondrial oxidation status, inflammation, energy metabolizing enzymes, oncogenic and apoptotic markers in mice model of diisononyl phthalate-induced asthma - Kehinde, Samuel Abiodun; Olajide, Abosede Temitope; Akinpelu , Oyindamola Joy; Ogunsanya , Sanmi Tunde (Life Sciences, Medicine and Biomedicine, 2023)
Primary plasticizer used in polyvinyl chloride is diisononyl phthalate (DiNP) and exposure to DiNP has been associated with the development of asthma and allergies. In the current study, how DiNP alters pulmonary antioxidant status, inflammation, energy metabolizing enzymes, oncogenic and apoptotic markers in DiNP-induced asthmatic mice was examined. Male BALB/c mice (n=20, 20-30 g) were divided into 2 groups of 10 mice each: group 1 (control) received saline (0.2ml/kg) orally for 23 days, and group 2 (DiNP) received 50 mg/kg DiNP (Intraperitoneal and intranasal) once per day. After the last administration, mice were sacrificed, lungs were removed and used for biochemical and histopathological analysis. DiNP treated mice experienced alterations in their lung histoarchitecture, levels of oncogenic and apoptotic factors, glycolytic, tricarboxylic acid cycle (TCA), and electron transport chain enzymes (ETC), antioxidant status, and inflammatory biomarkers. DiNP decreased the lungs levels of reduced glutathione and ascorbic acid, and the activities of superoxide dismutase, catalase, and glutathione-s-transferase. In the lungs of DiNP-treated mice compared to the control group, malondialdehyde and inflammatory biomarkers (nitric oxide and myeloperoxidase) were significantly greater (p<0.05). Furthermore, the activities of glycolytic enzymes hexokinase, aldolase, lactate dehydrogenase were downregulated with a concomitant increase in NADase (77%). TCA enzymes and ETC enzymes were significantly reduced as well. CAS-3, p53, Bax, c-MYC, K-Ras increased by 65%, 51%, 70%, 59% and 82% respectively while BCL-2 decreased by 74%. Histopathological analysis revealed distortion of the airway structure characterized by inflammatory cell infiltration, oedema, hemorrhage, and constricted alveoli space. Exposure to DiNP caused oxidative stress which promotes lung inflammation via depletion of antioxidants, pulmonary energy transduction enzymes, levels of oncogenic and apoptotic factors were impaired as well, suggesting that the lungs may not be able to perform its morphological and physiological functions effectively.